Titania aerogels: Preparation and photocatalytic tests - B. Malinowska; J. Walendziewski; D. Robert; J. V. Weber; M. Stolarski (International Journal of Photoenergy)
Titania aerogels are suggested as promising photocatalysts [1]. In the present study aerogels were synthesised by sol-gel method combined with supercritical drying. Tetraisopropyl orthotitanate was used as a precursor, anhydrous methanol and isopropanol as solvents. Three aerogels were prepared using different ways of synthesis. Volumes and surface areas of micro- and mesopores of each aerogel were determined. XRD and SEM analyses were carried out. For comparison analyses were also performed for TiO2 P25 Degussa. Aerogels' BET surface areas ranged from 73 to 96 m2g-1. They indicate the crystalline structure of anatase. Finally photocatalytic tests were performed using water solution of p-chlorophenol and 4-hydroxybenzoic acid. Experiments were carried out in the Solar box simulating sun irradiation and on location. Aerogel Z513 prepared using 30% of precursor (tetraisopropyl orthotitanate) in isopropanol as a solvent indicates the best photocatalytic activity towards p-chlorophenol while Z516 prepared using 60% of precursor in methanol towards 4-hydroxybenzoic acid.